Effect of Time and Storage Conditions on the Stability of Citronellal Lotion - Puspita, Fitria; Roziafanto, Ahmad Nandang; Saragih, Libora (Universitas Insan Cendekia Mandiri, 2025)
Commercial mosquito repellent lotion containing citronellal was tested for its stability to evaluate changes in the physical and chemical properties of the lotion at various times and storage condistions. This study used three variations of storage conditions; at 25°C, 30°C, 50°C, and sun exposured condition. Storage was carried out for 3 months and testing was carried out once a month for each storage condition. The lotion stability parameters tested included pH, viscosity, and citronellal content. Acidity measurement was carried out using a pH meter. Viscosity measurement was carried out using a Brookfield spindle helipath 96 viscometer at a speed of 12 rpm, while citronellal content measurement was carried out using gas chromatography. The results showed that storage time and temperature had a significant effect on the stability of citronellal lotion. The longer the lotion was stored, the viscosity and citronellal content decreased. In addition, higher storage temperatures also accelerated the decline in lotion stability, showed by significant changes in viscosity and citronellal content. Meanwhile, the pH of the lotion did not change significantly at each variation of storage time and conditions. Keywords: mosquito, repellant, citronellal, stability.